2013
DOI: 10.1098/rsif.2012.1053
|View full text |Cite
|
Sign up to set email alerts
|

In vitro and in vivo investigations on the effects of low-density lipoprotein concentration polarization and haemodynamics on atherosclerotic localization in rabbit and zebrafish

Abstract: Atherosclerosis (AS) commonly occurs in the regions of the arterial tree with haemodynamic peculiarities, including local flow field disturbances, and formation of swirling flow and vortices. The aim of our study was to confirm low-density lipoprotein (LDL) concentration polarization in the vascular system in vitro and in vivo, and investigate the effects of LDL concentration polarization and flow field alterations on atherosclerotic localization. Red fluorescent LDL was injected into optically transparent Flk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 45 publications
3
18
0
Order By: Relevance
“…Furthermore, the LDL concentration at the artery bifurcations, where lipid deposits tend to accumulate, was significantly elevated compared to the linear areas of the vasculature. Consistent with our findings, the injected DiI-LDL accumulated in the caudal vein 3 days after injection [28]. …”
Section: Modeling Early Processes Of Atherosclerosis In Hypercholestesupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, the LDL concentration at the artery bifurcations, where lipid deposits tend to accumulate, was significantly elevated compared to the linear areas of the vasculature. Consistent with our findings, the injected DiI-LDL accumulated in the caudal vein 3 days after injection [28]. …”
Section: Modeling Early Processes Of Atherosclerosis In Hypercholestesupporting
confidence: 92%
“…Xie et al injected a red fluorescent DiI-LDL into flk1:EGFP embryos and recorded the hemodynamics of the injected LDL using a laser scanning confocal microscope [28]. The authors found that the concentration of LDL was increased at the vascular wall compared to the center of the lumen, suggesting a polarized LDL distribution.…”
Section: Modeling Early Processes Of Atherosclerosis In Hypercholestementioning
confidence: 99%
“…In previous works, we demonstrated the important contribution to cell migration and adhesion by cytoskeletal reorganization associated with focal adhesions assembly when the cells overexpressed Id1 [14], stimulated by various concentrations of oxLDLs (oxidized low-density lipoprotein) at static conditions [15 -17], placed on surfaces with different degrees of wettability [18,19] or LDL treatment under shear stress [20,21]. It is well established that cells use actin polymerization coupled with integrin-mediated adhesion to generate lamellipodial protrusions at the cell front to migrate on two-dimensional substrates [2].…”
mentioning
confidence: 99%
“…We therefore investigated if nanoparticle accumulation is spontaneously increased in the non-uniform shear stress region in vitro, as described for the spontaneous in vivo accumulation of LDL particles in these regions [14]. For this purpose, we seeded the endothelial cells in the bifurcating flow-through cell culture slides, which simulate the non-uniform shear stress gradient at arterial bifurcations [12].…”
Section: An External Magnetic Force Allows Targeted Spion Accumulatiomentioning
confidence: 99%